Clinical and laboratory manifestations of dengue fever cases at subang regional general hospital - Rifky R Sulthan; Yoke Ayukarningsih; Siska T Pratiwi; Diana Rosifah (ACTA Medical Health Sciences, 2025)
Dengue fever remains a major public health problem in Indonesia, particularly among children. Early recognition of clinical manifestations, supported by laboratory findings, is crucial for diagnosis, monitoring disease progression, and preventing severe complications. This study aimed to describe the clinical manifestations and laboratory findings of dengue fever cases in children. A cross-sectional study design was used, based on medical records of all pediatric patients aged 0–18 years who werediagnosed with dengue infection at Subang Regional Hospital from January to December 2024. Total sampling yielded 197 cases that met the inclusion criteria. Most patients were aged 6–18 years (73.1%) and male (57.4%). The highest incidence occurred in March (20.8%). The most common clinical manifestations were fever (100%), abdominal pain (61.9%), nausea (61.4%), vomiting (53.8%), and headache (37.1%). Warning signs were identified in 46.2% of patients, with persistent vomiting and abdominal pain being the most frequent. Laboratory findings showed thrombocytopenia (75.0%) and leukopenia (62.5%), particularly in the 6–18 age group, while anemia was most common in infants aged 0–1 year (92.3%). Serological examinations showed all patients were NS1 positive at initial testing, with IgM and IgG detected in subsequent examinations, indicating progression from the acute to the convalescent phase. These findings highlight the importance of integrated clinical and laboratory evaluation for early detection and appropriate management of dengue fever.   DOI : 10.35990/amhs.v4n2.p77-86   REFERENCES Syamsir, Daramusseng A. Analisis spasial efektivitas fogging di wilayah kerja Puskesmas Makroman, Kota Samarinda. JNIK. 2018;1(2):1–7. Podung GCD, Tatura SNN, Mantik MFJ. Faktor risiko terjadinya sindroma syok dengue pada demam berdarah dengue. JBM. 2021;13(2):161–166. Ubaidillah, Kurniawan D. Faktor risiko yang mempengaruhi terjadinya kejadian demam berdarah dengue (DBD) di Puskesmas Sewon II Bantul. PHJ. 2020;11(1):7–12. Rahma FA, Rahayu DFS, Prawira LY, Nandini M, Bariyah RA. Faktor risiko aspek lingkungan dan aspek perilaku terhadap kejadian demam berdarah dengue (DBD) di wilayah kerja Puskesmas Sukmajaya, Kota Depok tahun 2022. JoPHJ. 2023;2(3):91–101. Sumampouw OJ. Epidemiologi demam berdarah dengue di Kabupaten Minahasa, Sulawesi Utara. SRJPH. 2020;1(1):1–8. Nanda M, Saragih PA, Nasution DH, Daulay A, Sari DP, Ridho NU. Analisis pengendalian faktor risiko dan vektor kejadian demam berdarah dengue. FJIK. 2023;2(2):111–116. Anggraini DR, Huda S, Agushybana F. Faktor perilaku dengan kejadian demam berdarah dengue (DBD) di daerah endemis Kota Semarang. JIKK. 2021;12(2):344–349. World Health Organization (WHO). Disease outbreak news: Dengue—Global [Internet]. 2024 [diakses 2 Apr 2025]. Tersedia pada: https://www.who.int/emergencies/disease-outbreak-news/item/2023-DON518 World Health Organization (WHO). Dengue Bulletin [Internet]. 2021 Mar [diakses 2 Apr 2025]. Tersedia pada: https://www.who.int/publications/i/item/ISSN0250-8362 Tansil MG, Rampengan NH, Wilar R. Faktor risiko terjadinya kejadian demam berdarah dengue pada anak. JBM. 2021;13(1):90–99. Kementerian Kesehatan Republik Indonesia. Survei Kesehatan Indonesia (SKI) dalam angka: data akurat, kebijakan tepat [Internet]. 2023 [diakses 7 Jan 2025]. Tersedia pada: https://kemkes.go.id/id/survei-kesehatan-indonesia-ski-2023 Wila RW, Nusa R. Gambaran klinis dan respon imun penderita demam berdarah dengue di Rumah Sakit Kristen Lindi Mara Sumba Timur selama bulan Januari sampai dengan Desember 2018. BALABA. 2020;16(2):209–216. Indriyani DPR, Gustawan IW. Manifestasi klinis dan penanganan demam berdarah dengue grade 1: sebuah tinjauan pustaka. ISM. 2020;11(3):1015–1019. Ahmad ZF, Mongilong NS, Kadir L, Nurdin SSI, Moo DR. Perbandingan manifestasi klinis penderita demam berdarah. IJPE. 2023;3(1):143–153. Dahlan MS. Besar sampel dan cara pengambilan sampel dalam penelitian kedokteran dan kesehatan. In: Suslia A, editor. Edisi ke-3. Jakarta: Salemba Medika; 2010. p. 155–157. Kementerian Kesehatan Republik Indonesia. Pedoman nasional pelayanan kedokteran: tata laksana infeksi dengue anak dan remaja [Internet]. Indonesia: Kemenkes RI; 2021 May 3. Tersedia pada: https://kemkes.go.id/id/pnpk-2021-infeksi-dengue-anak-dan-remaja Prayitno A, Taurel AF, Nealon J, Satari HI, Karyanti MR, Sekartini R, et al. Dengue seroprevalence and force of primary infection in a representative population of urban dwelling Indonesian children. PLoS Neglected Tropical Diseases. 2017;11(6). Khan MAS, Al Mosabbir A, Raheem E, Ahmed A, Rouf RR, Hasan M, et al. Clinical spectrum and predictors of severity of dengue among children in 2019 outbreak: A multicenter hospital-based study in Bangladesh. BMC Pediatrics. 2021;21(1). Burattini MN, Lopez LF, Coutinho FAB, Siqueira JB, Homsani S, Sarti E, et al. Age and regional differences in clinical presentation and risk of hospitalization for dengue in Brazil, 2000–2014. Clinics. 2016;71(8):455–463. Kumar M, Verma R, Nirjhar S, Singh M. Dengue in children and young adults: A cross-sectional study from the western part of Uttar Pradesh. Journal of Family Medicine and Primary Care. 2020;9(1):293. Tchuandom SB, Tchadji JC, Tchouangueu TF, Biloa MZ, Atabonkeng EP, Fumba MIM, et al. A cross-sectional study of acute dengue infection in paediatric clinics in Cameroon. BMC Public Health. 2019;19(1):958. Lee YH, Hsieh YC, Chen CJ, Lin TY, Huang YC. Retrospective seroepidemiology study of dengue virus infection in Taiwan. BMC Infectious Diseases. 2021;21(1). Kesetyaningsih TW. Distribution of dengue hemorrhagic fever (DHF) in regards to age and sex in Sleman, Yogyakarta, Indonesia. 2019. Zohra T, Din M, Ikram A, Bashir A, Jahangir H, Baloch IS, et al. Demographic and clinical features of dengue fever infection in Pakistan: A cross-sectional epidemiological study. Tropical Diseases, Travel Medicine and Vaccines. 2024;10(1). Taufik A, Hasibuan PA, Putri FD, Wulandari A, Mutika WT, Lisa M. Case series: Angka kematian demam berdarah dengue berdasarkan jenis kelamin di Jawa Barat. Jurnal Kesmas Untika Luwuk: Public Health Journal. 2024;15(2):124–133. Setrkraising K, Kittitrakul C. Gastrointestinal manifestations and prognostic factors for severe dengue in Thai children. The American Journal of Tropical Medicine and Hygiene [Internet]. 2024 [diakses 19 Jul 2025];112(3):642–647. Tersedia pada: https://pubmed.ncbi.nlm.nih.gov/39719114/ Afroze S, Shakur S, Wahab A, Shakur S. Clinical profile of dengue and predictors of its severity among children. American Journal of Pediatrics. 2019;5(4):219. Karyanti MR, Uiterwaal CSPM, Hadinegoro SR, Widyahening IS, Saldi SRF, Heesterbeek JAPH, et al. The value of warning signs from the WHO 2009 dengue classification in detecting severe dengue in children. The Pediatric Infectious Disease Journal. 2024;43(7):630–634. Islam S, Khan MAS, Badal MFA, Khan MZI, Gozal D, Hasan MJ. Clinical and hematological profiles of children with dengue residing in a non-endemic zone of Bangladesh. PLoS Neglected Tropical Diseases. 2022;16(10). Bodinayake CK, Tillekeratne LG, Nagahawatte A, Devasiri V, Kodikara Arachchi W, Strouse JJ, et al. Evaluation of the WHO 2009 classification for diagnosis of acute dengue in a large cohort of adults and children in Sri Lanka during a dengue-1 epidemic. PLoS Neglected Tropical Diseases. 2018;12(2). Prieto-Torres AE, Medina-Lozano LJ, Ramírez-Ávila JD, Faccini-Martínez ÁA. Utility of VIDAS® dengue diagnostic assays to differentiate primary and secondary dengue infection: A cross-sectional study in a military hospital from Colombia. Tropical Medicine and Infectious Disease. 2025;10(2). Versiani AF, Kaboré A, Brossault L, Dromenq L, dos Santos TMIL, Milhim BHGA, et al. Performance of VIDAS® diagnostic tests for the automated detection of dengue virus NS1 antigen and of anti-dengue virus IgM and IgG antibodies: A multicentre, international study. Diagnostics. 2023;13(6). Premazzi Papa M, Mendoza-Torres E, Sun P, Encinales L, Goulet J, Defang G, et al. Dengue NS1 antibodies are associated with clearance of viral nonstructural protein-1. Journal of Infectious Diseases. 2024;230(6):e1226–e1234. Anika US, Islam M, Nur Mou FE, Saha M, Deb A, Tui RR, et al. The 2023 dengue outbreak in Bangladesh: Exploring the epidemiology in hospitalized patients. The American Journal of Tropical Medicine and Hygiene. 2024;110(6):1165–1171. Felix AC, Romano CM, Campos Centrone C, Rodrigues CL, Villas-Boas L, Araújo ES, et al. Low sensitivity of NS1 protein tests evidenced during a dengue type 2 virus outbreak in Santos, Brazil, in 2010. Clinical and Vaccine Immunology. 2012;19(12):1972–1976.